PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS X SMA NEGERI 1 2x11 ENAM LINGKUNG - Hasanah, Devy (Departemen Matematika, 2024)
Understandings ideas is one of the mathematical ability that students needs to acquire. The results of the observation at SMA Negeri 1 2x11 Enam Lingkung indicate a low level of students understanding of mathematical conceptss. Geogebra-assisted Problem-Based Learning (PBL) can help overcome this problem. This study examines the understandings of mathematical concepts of X grade students of SMA Negeri 1 2x11 Enam Lingkung who are implemented Problem Based Learning (PBL) assist by geogebra and compares it with the direct learning model. This study also tracked students understandings of mathematical concepts during the implementation of the geogebra-assisted PBL model. A posttest-only non-equivalent control group design was used in this quasi-experimental and descriptive study. Learners who learned using geogebra-assisted PBL had a better understandings of mathematical concepts compared to the application of direct learning.Keywords– Mathematical Concepts Understandings, Hands-On Learning, Problem Based Learning